Peran dan Sumber Daya Cloud-Based Management System Pada Perusahaan - Najmi Afifah; Muhammad Irwan Padli Nasution (Getpress Management Journals, 2025)
Information system transformation is a crucial step for small businesses in facing rapid technological developments. However, limited costs and technical skills are often major barriers to adopting new technologies. This study aims to evaluate the cost efficiency of implementing a Cloud-Based Management System (CBMS). Cloud-based systems have been proven to reduce operational costs, improve accessibility, and accelerate organizational performance through data automation and integration. The success of a CBMS implementation depends on organizational readiness and human resource training. Despite offering many benefits, data security remains a major challenge, necessitating the selection of a cloud service provider with robust security systems. Overall, a CBMS provides an effective solution for small businesses to improve operational efficiency and support ongoing digital transformation.